Susceptibility of Wiseana species to diflubenzuron and implications for field applications - Ferguson, C.M. (New Zealand Plant Protection, 2000)
Porina control using diflubenzuron is popular due to its low cost and benign environmental effects The level of control in Otago and Southland however can be variable and may be associated with species diversity in the region In this investigation larvae of Wiseana cervinata W copularis W jocosa and W mimica were exposed to diflubenzuron in two laboratory bioassays All species were killed with small larvae killed more quickly than large There were only minor differences in susceptibility between species Adult flights at three sites showed variation in the main flight period suggesting that larvae in pasture in autumn would cover a wide size range This was confirmed by field sampling The timing and frequency of diflubenzuron applications should be considered in conjunction with the phenology of adult flight and subsequent larval development and climatic conditions affecting larval survival